The Influence of Product Quality and Service Quality on Makeup Artist (MUA) Consumer Satisfaction in Bengkulu City (Case Study of Fhadinalove Mua Consumers in Bengkulu City) - Melati, Bella Syofina; Ratnawili, Ratnawili (Jurnal Fokus Manajemen, 2024)
This research aims to determine the influence of product quality and service quality on consumer satisfaction of Fhadinalove MUA in the city of Bengkulu.This study uses a quantitative approach. The population in this study is all consumers at Fhadinalove MUA whose number is unknown. The sample in this study uses the Non Probability Sampling Technique, namely a sampling technique that does not provide an equal opportunity for each element or member of the population to be selected as a sample and the method used namely Accidental Sampling, the sample used was 90 respondents, and the data collection technique was by distributing questionnaires. This research uses several data analysis techniques. These include: Instrument testing, classical assumption testing, analysis of respondent responses, multiple linear regression analysis, coefficient of determination and hypothesis testing.Based on the results of multiple linear regression analysis, the equation form Y = 2.841 + 0.243 (X1) + 0.366 (X2). The research results and hypothesis show that product quality from the t test results shows thit>ttable values (3.047 > 1.987) and (sig α = 0.003 < 0.050). Service quality t test results show thit>ttable (7.403 > 1.987) and (sig α = 0.000 < 0.050). partially, the two variables product quality and service quality have a significant influence on consumer satisfaction. From the research results and hypotheses, it also shows that together product quality and service quality have an influence on consumer satisfaction, seen from the results of the f test showing the values, namely (126.422 > 3.9505) and (sig α = 0.000 < 0.050).